Oral Health and the Stroke Survivor - Donna Morris; June Sadowsky (Association of American Medical Colleges, 2013)
Abstract This module includes a narrated PowerPoint with embedded video clips, as well as a non-narrated PowerPoint presentation, both of which provide a review of the numerous effects a cerebrovascular accident can have on the oral cavity. Common oral hygiene practices of nursing staff that are inadequate and may be detrimental to oral health are explained and therapeutic alternatives are presented and demonstrated. The effects of poor oral hygiene on overall systemic health are outlined along with an oral hygiene regimen and demonstration for long-term care patients and those affected by stroke. Therapeutic oral products that enhance the oral health of long-term care patients and those affected by stroke along with procedures for their use are also explained and presented in the video. The presentation and video will prepare a non-dental professional to provide routine oral care. Lastly, ways that dental, medical and nursing professionals can be influential in changing the standard of care for long-term care patients are suggested. The module can be used for self-instruction in which the learner can view the presentation in Articulate with the capability to navigate to specific slides or videos. The presentation and/or the reading assignment can be followed by completion of the ten self-assessment questions. The presentation can be placed online or on CD for use. The presentation in Articulate or the non-narrated PowerPoint presentation could be used as part of a lecture on oral health for stroke survivors with the assessment questions used as review or as part of an exam. The power point has speaker notes included for use in presenter mode. A separate Word document with the speaker notes is also provided.